2017
DOI: 10.7224/1537-2073.2016-099
|View full text |Cite
|
Sign up to set email alerts
|

Project Extension for Community Healthcare Outcomes (ECHO) in Multiple Sclerosis

Abstract: Background: A pilot program using the Project Extension for Community Healthcare Outcomes (ECHO) model was conducted for multiple sclerosis (MS) clinicians in the Pacific Northwest. The pilot was a collaboration between the National Multiple Sclerosis Society and faculty at the University of Washington. The goal was to determine the feasibility of using this telehealth model to increase the capacity and capability of clinicians in rural areas to treat people with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 11 publications
4
31
0
Order By: Relevance
“…Change in confidence and self-efficacy focused on whether providers reported greater confidence in ability to diagnose and/or treat patients following EELM participation. 17,23,26,30,32,34,41,48,51,52,56,71 Metrics along these lines were reported in most studies, ranging from selfreported changes following participation, 32 to within-subjects change from baseline to endline, 48 to between-subjects comparisons in perceived competence, 30 including in one randomized controlled trial (RCT). 26 In most instances, results were positive and significant; a notable exception came from the RCT on chronic pain management.…”
Section: Provider-related Outcomesmentioning
confidence: 99%
“…Change in confidence and self-efficacy focused on whether providers reported greater confidence in ability to diagnose and/or treat patients following EELM participation. 17,23,26,30,32,34,41,48,51,52,56,71 Metrics along these lines were reported in most studies, ranging from selfreported changes following participation, 32 to within-subjects change from baseline to endline, 48 to between-subjects comparisons in perceived competence, 30 including in one randomized controlled trial (RCT). 26 In most instances, results were positive and significant; a notable exception came from the RCT on chronic pain management.…”
Section: Provider-related Outcomesmentioning
confidence: 99%
“…In a previous publication, we comprehensively described the Project ECHO concept, our adaptation to MS, objective data describing the providers who participated in the pilot study (clinical specialty, MS experience, geographic location), the topics covered during the program, and metrics of participation and satisfaction with the program. 7 In contrast, the present article focuses exclusively on the case consultation portion of the program and summarizes qualitative feedback obtained via exit interviews.…”
Section: Overviewmentioning
confidence: 99%
“…6 Geographic, financial, and health-related barriers limit the ability of patients in underserved areas to travel to MS specialty centers, thus creating the need for improvements in the care that individuals with MS receive in these underserved areas. In a previous publication, 7 we described our successful adaptation of an approach to accelerating the transfer of knowledge from content experts to rural providers who then develop an enhanced level of clinical understanding and confidence, allowing them to serve as local experts in MS care. In this program, called MS Project ECHO (Extension for Community Healthcare Outcomes), 8 providers who care for individuals with MS (the "participants") in underserved areas join a weekly videoconference that includes a brief didactic focused on key information necessary to provide high-quality care, followed by case consultation and discussion.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(University of New Mexico, 2020) This includes one prior translation of the Project ECHO model for management of patients with MS, which resulted in participants self-reporting improvement in perceived knowledge, expertise, and provider behavior. (Johnson et al, 2017;Alschuler et al, 2019) A related demonstration project also showed the model could be used to aid an international audience in improving their knowledge of DMTs for MS that were newly approved in their country but had been utilized for a number of years in the U.S. (Alschuler et al, 2016) Project ECHO has been previously recommended as a model for facilitating the rapid sharing of knowledge during global health crises (e. g., Zika crisis (Heard-Garris et al, 2017)) and has preliminary evidence for utility with the MS healthcare community. Thus, the National MS Society sought to leverage the model to expedite knowledge sharing for the management of persons living with MS during the COVID-19 pandemic ("ECHO MS COVID-19 Response Clinic").…”
Section: Introductionmentioning
confidence: 99%